Legal problems of the order classifications immovable objects of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The legal problems ordered of classifications immovable objects are examined in the scientific article. Duringresearch stopped for the certain lacks of civil law, suggestions came into question for the improvement oflaw on state registrations of rights for the real estate.Keywords: real estate, land, condominium, building.